Wild Chimpanzees Infected with 5 Plasmodium Species - Kaiser, Marco (Centers for Disease Control and Prevention, 2010)
Data are missing on the diversity of Plasmodium spp. infecting apes that live in their natural habitat, with limited possibility of human-mosquito-ape exchange. We surveyed Plasmodium spp. diversity in wild chimpanzees living in an undisturbed tropical rainforest habitat and found 5 species: P. malariae, P. vivax, P. ovale, P. reichenowi, and P. gaboni.